Dynamics of ZnO laser produced plasma in high pressure argon - LUNNEY, JAMES (My University, 2011)
Pulsed laser deposition of ZnO in high pressure gas offers a route for the catalyst-free preparation of ZnO nanorods less than 10 nm in diameter. This paper describes the results of some experiments to investigate the laser plume dynamics in the high gas pressure (5 ? 103 - 104 Pa) regime used for PLD of ZnO nanorods. In this regime the ablation plume is strongly coupled to the gas and the plume expansion is brought to a halt within about 1 cm from the target. A 248 nm excimer laser was used to ablate a ceramic ZnO target in various pressures of argon. Time- and space-resolved UV/visible emission spectroscopy and Langmuir probe measurements were used to diagnose the plasma and follow the plume dynamics. By measuring the spatial profiles of Zn I and Zn II spectral lines it was possible to follow the propagation of the external and internal shock waves associated with the interaction of the ablation plume with the gas. The Langmuir probe measurements showed that the electron density was 109-1010 cm?3 and the electron temperature was several eV. At these conditions the ionization equilibrium is described by the collisional-radiative model. The plume dynamics was also studied for ZnO targets doped with elements which are lighter (Mg), comparable to (Ga), and heavier (Er) than Zn, to see if there is any elemental segregation in the plume.
PUBLISHED
Keywords: Fluids and plasma physics; ZnO nanorods; Nanoscience & Materials